A Study on Astronomical Cycle Identification and Environmental Response Characteristics of Lacustrine Deep-Water Fine-Grained Sedimentary Rocks: A Case Study of the Lower Submember of Member 3 of Shahejie Formation in Well Fanye-1 of Dongying Sag, Bohai Bay Basin, China. (28th June 2021) - Yu, Ledan; Peng, Jun; Xu, Tianyu; Wang, Yubin; Han, Haodong
Abstract : With the further exploration and development of shale oil and gas, cycle division of fine-grained sedimentary rock strata has been increasingly highly focused on by scholars. Owing to the application of the theory of classical sequence stratigraphy based on water depth changes and its technical methods being unsatisfactory in the isochronous division and correlation of deep-water fine-grained sedimentary strata, the cycle division of fine-grained sedimentary rock strata has always been a difficult point in the study of sequence stratigraphy. In this paper, the Milankovitch cycle recorded from the study interval and the environment response characteristics were studied, with the lacustrine shale in the lower third submember of the Paleogene Shahejie Formation (lower Es3 submember) in Well Fanye-1 of the Dongying sag, Bohai Bay Basin, as the object of study, by such technical means as thin section identification and X-ray whole rock diffraction, based on such data as logging data and geochemistry, combining the methods of spectral analysis, wavelet transform, and modulus extremum. The results showed that the stratigraphic cycle thicknesses caused by long eccentricity, short eccentricity, and obliquity periods were 38.95 m, 12.98 m, and 4.10 m, respectively, and a total of 16 short eccentricity periods and 4.5 long eccentricity periods were identified in the study interval. Thus, it was further calculated that the sedimentation time was approximately 1.905 Ma, and the average sedimentation rate was estimated to be 0.105 m/ka. Studies have shown that the sedimentary environment of lacustrine fine-grained sedimentary rocks is controlled by the astronomical period, based on which the climate as a whole changes from relatively dry and cold to warm and wet when the eccentricity increases. The identification of the Milankovitch cycle of the lacustrine fine-grained sedimentary strata will provide references for the study of high frequency sequence and the division of high-resolution sequence strata, which can effectively solve the scientifically difficult isochronous division and correlation of lacustrine shale strata.